Use of social media to communicate sport science research - Williams, J. H. (International Journal of Sports Science and Coaching, 2011)
Scientists and coaches acknowledge that an information gap exists between research and practice. Communication barriers hinder applying research findings in a timely manner. This investigation examined the usefulness of social media to communicate sport science research. A Facebook fan page and a website dedicated to translating soccer-related research (Science of Soccer Online, SSO) were established. T he Facebook fan page accounted for the largest number referrals to the SSO website. Those accessing SSO via Facebook spent nearly 5 min on the site and viewed 1-2 articles per visit. A survey about the usefulness of the Facebook indicated that most respondents noticed and utilized links posted on the Facebook fan page. Survey participants also indicated that they used the fan page to access the SSO website. The results suggest a Facebook fan page that provides links to practical scientific information is a potentially useful means of communicating sport science to practitioners.